Do capital market training, online facilities and social environment matter in investment decision / Yuni Nustini … [et al.] - Nustini, Yuni; Mohd Suffian, Mohd Taufik; Zakaria, Nor Balkish; Mohd Sanusi, Zuraidah; Wan Mohd Radzi, Wan Shahriah (Universiti Teknologi MARA, 2021)
This study aimed to determine if capital market training, on-line facilities, social environment, and a minimum amount of investment affect Indonesian and Malaysian university-students’ decisions in investing in the capital markets of each country, as they are potential smart investors. Based on 229 respondents from both countries, a survey was conducted comprising 24 questions. Respondents were selected using they random sampling method. The results found that capital market training and on-line facilities were not factors that influenced university students’ decisions in Indonesia and Malaysia in making investment in the capital markets. The other two variables, social environment and a minimum amount of investment proved influential. The mediating variable, investment interest partially influenced the relationship between social environment and a minimum amount of investment-to-investment decision, but did not mediate capital market training and on-line facilities to the investment decision.